Sexual Desire in Women: Paradoxical and Non-Linear Associations with Depression and Anxiety. (1st August 2022) - Bittoni, C; Kiesner, J
ABSTRACT: Introduction: Previous studies aimed at defining the relationship between high levels of negative mood and sexual desire have shown that, in addition to people describing an expected decrease in sexual desire, some people report an unexpected increase in sexual desire when depressed or anxious (referred to as a "paradoxical effect", Bancroft et al., 2003). However, these past findings are based on self-inferred causal attributions and retrospective, one-time measurements. Moreover, tests of these associations at the low extreme of negative mood have not been previously conducted. Objective: The aim of the present study was to replicate and expand previous findings regarding paradoxical effects of negative mood on sexual desire (Bancroft et al., 2003; Lykins, Janssen & Graham, 2006), by analyzing the associations between negative mood and sexual desire across the entire range of depression and anxiety symptoms. Moreover, to address previous limitations, we sought to test for replication using methods that are unaffected by recall bias, and that don't require participants to infer causal associations between their mood and sexual desire. Methods: A sample of n=213 university-aged women completed daily questionnaires for two full menstrual cycles (M = 58 daily reports per participant). Measurement included changes in sexual desire, as well as psychological changes (anxiety and depression) and other symptoms associated with the menstrual cycle. Multilevel modeling with random intercepts and slopes, were used to test for individual differences in linear and non-linear associations between mood symptoms and changes in sexual desire. Cluster analyses were used to identify different patterns of change in sexual desire associated with different levels of mood. Results: Previous findings were successfully replicated. Specifically, high levels of depression were associated with increased sexual desire in 12% of the sample (paradoxical association), and high levels of anxiety were associated with increased sexual desire in 20% of the sample (paradoxical association). Thus, in addition to women who showed either no significant changes or a decrease in sexual desire when depressed or anxious, results confirmed the presence of paradoxical associations between high levels of negative mood and sexual desire (see shaded area on Fig.1). Interestingly, these between-group paradoxical effects were also present at low levels of negative mood. That is, at low levels of negative mood some women reported increased sexual desire while others reported decreased sexual desire. Moreover, for both depression and anxiety, analyses revealed three clusters of women presenting different patterns of change in sexual desire across different levels of mood symptoms. Specifically, results demonstrated the presence of within-person paradoxical associations, whereby, there are some women for whom both low and high levels of negative mood are associated with the same change (an increase or a decrease) in sexual desire. These groups are labeled "Positive Paradoxical" and "Negative Paradoxical" in Fig.1. Conclusions: Results from the present study underline the importance of considering individual variability when studying sexual desire. Multiple mechanisms, based on personality traits, learning, autonomic activity, or situational factors, might moderate the relationship between mood and sexual desire. A new integrative theoretical framework is proposed to interpret these results (see Figure 2). Disclosure: No